Design and fabrication of folding chair - Mohd Sani, Idris (2009)
This report is presents about the designing and fabrication of a folding chair. Based on the title that given of this project, the student has to create their own design of a folding chair and fabricate the product by individual. The main objective of this project is to design and fabricate a light weight folding chair that able to be used in various types of activities in daily life. There are a several scopes of this project those consist of fabricate an ergonomic folding chair, designing a folding chair that able to used for indoor and outdoor activities, make a few analysis on the product material, and carry out a survey after fabrication. The software that used for designing the concept of folding chair is AutoCAD. This software is able to provide the product drawing in two dimensional and three dimensional views. The concept that selected as final design and will develop for fabrication process is arm table folding chair. This concept is suitable to use for various types of activities such as seminar, campaign and relaxing. The materials that use for fabricate the folding chair is structural steel that come from ASTM-A36 type. This material is selected because it is hard, more strength and durable. The machining processes that used in this project are such as cutting, welding, drilling and grinding. Besides, there are several analyses design that built in this project. Those analyses are bending moment and stress analysis. Both analyses are purposes to determine the value of bending moment and stress towards the material when applied minimum and maximum load on the back rest and seat part of the folding chair. The minimum load that applied for this analysis is 80 kg and maximum load is 200 kg. . Besides, these analyses also used to measure the strength of material whether the material that used can withstand with the loads give. As the result of analyses, the materials that are structural steel ASTM-A36 can withstand with the loads given and safe to use for fabrication process. In addition, this project had carried out a survey in university area. That survey had carried out through by questionnaire form and its purpose to gathering the data about the folding that was fabricated and also to gathering the suggestions from respondent for improve the design of folding chair for future.